Human judgment : the SJT view - Brehmer, Berndt; Joyce, C. R. B. (Charles Richard Boddington), 1923- (Advances in psychology (Amsterdam, Netherlands), 1988)
There are four basic goals for research in SJT (Social Judgment Theory): - to analyze judgment tasks and judgmental processes; - to analyze the relations between judgmental systems (i.e. to analyze agreement and its structure), and between tasks and judgmental systems (i.e. to analyze achievement and its structure; - to understand how relations between judgmental systems and between judgmental systems and tasks come to be whatever they are (i.e. to understand processes of communication and learning and their effects upon achievement and agreement); - to find means of improving the relation between judgmental systems (improving agreement) and between judgmental systems and tasks (improving achievement).